(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2015)
The fungal infection is zoonotic infectious disease, caused by different species of dermatophytes. In this study, skin scrapings and hair samples were collected from cattle withÂ clinical symptoms of dermatophytosis. The collected samples were directly examined for fungalÂ elements by direct microscopy. Bergamot oil was shown to be a potent antimicrobial agent inÂ vitro against clinically important trichophyton verrucosum. In this study, the activities ofÂ bergamot natural essence on trichophyton verrucosum were investigated. The results indicatedÂ that the MICs (v/v) of the bergamot oil against the fungi Trichophyton verrucosum was 0.125.